From Gutenberg to the Global Information Infrastructure: Access to Information in the Networked World - Borgman, Christine L (Digital Libraries and Electronic Publishing, 2003)
Will the emerging global information infrastructure (GII) create a revolution in communication equivalent to that wrought by Gutenberg, or will the result be simply the evolutionary adaptation of existing behavior and institutions to new media? Will the GII improve access to information for all? Will it replace libraries and publishers? How can computers and information systems be made easier to use? What are the trade-offs between tailoring information systems to user communities and standardizing them to interconnect with systems designed for other communities, cultures, and languages?This book takes a close look at these and other questions of technology, behavior, and policy surrounding the GII. Topics covered include the design and use of digital libraries; behavioral and institutional aspects of electronic publishing; the evolving role of libraries; the life cycle of creating, using, and seeking information; and the adoption and adaptation of information technologies. The book takes a human-centered perspective, focusing on how well the GII fits into the daily lives of the people it is supposed to benefit.Taking a unique holistic approach to information access, the book draws on research and practice in computer science, communications, library and information science, information policy, business, economics, law, political science, sociology, history, education, and archival and museum studies. It explores both domestic and international issues. The author's own empirical research is complemented by extensive literature reviews and analyses.